Crack growth micro-mechanisms in the IN718 alloy under the combined influence of fatigue, creep and oxidation - Prakash, D; Walsh, M; Maclachlan, D; Korsunsky, A (2009)
The objective of the present study is to review the different phenomena responsible for crack growth in the IN718 nickel-base superalloy under the combination of fatigue, creep and oxidation. We review the descriptions of the micro-mechanisms found in the literature, with a special emphasis on the time-dependent effects. The changes in the microscopic appearance of fracture surfaces due to the variations in the temperature, frequency, dwell time, microstructure and partial pressure of oxygen are considered. Elucidation of these microscopic aspects of crack growth requires establishing a connection with macroscopic conditions and parameters of crack growth, and these topics are touched upon in the present review insofar it is necessary. The review allows the identification of important parameters that control component durability, and need to be included in fatigue crack growth modelling for the development of better predictive lifing assessments. © 2009 Elsevier Ltd. All rights reserved.